Is it possible to improve the results of cancer treatment without treating cancer? - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2004)
Cancer clinical trials frequently concentrate only on methods of destruction of tumor cells. However, the majority of cancer patients die of other, only partially related causes such as various infections. Furthermore, utilization of more and more aggressive therapeutic methods, that on one hand increase the frequency of patients cured of cancer but on the other hand have very significant adverse effects requires methods of better control of these effects that sometimes are even lethal. This may mean that it is possible to prolong the life of cancer patients also by improving methods of control of such complications. Even without the prolongation of life, if we remove suffering from that life we would provide an opportunity for a better use of limited lifetime. In recent years new antibiotics, antimycotic and antiviral agents have been discovered and introduced to the practice or at least to the clinical trials. Moreover, new analgesics or new preparations of older agents have been introduced. Methods of control of such complications as anemia, neoplastic bone defects, hormonal disturbances in women have been improved as well. Furthermore, there is also a progress concerning methods of control of adverse reactions to anticancer drugs. There are new formulations of growth factors and drugs that directly and with good selectivity protect healthy cells from deleterious effects of radiation and chemotherapy. This list is far from being complete. We note progress in every aspect of cancer care and currently we are trying to focus our attention on the significance of this part of management to the life and its quality in patients with cancer.